STATE REGULATION OF NON-FINANCIAL REPORTING IN RUSSIA AND THE WORLD - P. Shcherbachenko (Вестник университета)
The article deals with the main directions of development of non-nancial reporting in Russia and the world. The article contains an analysis of the issue of non-nancial reporting in the Russian Federation. The author gives considerable attention to the issues of state regulation of non-nancial reporting in Russia. Information is presented on the stages of preparation of the concept of the development of public non-nancial reporting in Russia and the application of the European Union (EU) Directive on the disclosure of non-nancial information in the countries of the EU. The conclusion is made that it is necessary to rene the regulatory and legal framework for corporate social responsibility and focuses on training specialists in the preparation of non-nancial reports.